STUDI KASUS PERILAKU GHASAB SANTRI PONDOK PESANTREN - Ismawan, Rudi Izal; Wibowo, Agus; Nurlaila, Siti (Universitas Muhammadiyah Metro, 2025)
The purpose of this activity is to provide students with a full understanding of how the characteristics of ghasab behavior and the factors that cause it and also how to prevent this ghasab behavior. The type of research used is a case study and the data obtained by the researcher is through direct subject interviews and observation at the research site. The data subjects used were Ustadz of the Kesantrian section, students who had ghasab behavior, and students who were victims of ghasab behavior. The data analysis used in this study adopted the Miles and Huberman Models, Furthermore, checking the validity of the findings is carried out using source triangulation, namely the data produced is the same as from different sources. The result of this activity is that the students' efforts to prevent ghasab behavior, improvement to regulations of Islamic boarding school, asatidz control, Islamic boarding school supervision of the behavior of students in the Islamic boarding school, and imposing sanctions on students who violate it.